Functional forms of hardening internal state variables in modeling elasto-plastic behavior - Dorgan, R.J.; Voyiadjis, G.Z. (Archives of Mechanics, 2007)
In this work use is made of functional forms of hardening state variables within a consistent thermodynamic formulation to model the elasto-plastic behavior of materials. The formulation is then numerically implemented using the developed plasticity model. In deriving the constitutive model, a local yield surface is used to determine the occurrence of plasticity. Isotropic hardening and kinematic hardening are incorporated as state variables to describe the change of the yield surface. The hardening conjugate forces (stress-like terms) are general nonlinear functions of their corresponding hardening state variables (strain-like terms) and can be defined basing on the desired material behavior. Various exponential and power law functional forms are studied in this formulation. The paper discusses the general concept of using such functional forms; however, it does not address the relevant appropriateness of certain forms to solve different problems. It is shown that, depending on the functions used, standard models known from the literature can be recovered. The use of this formulation in solving boundary value problems will be presented in future.